Effects of Biofouling on Hydrodynamic Behavior of a Semi-submersible Wind Turbine System (Proceedings of the European Wave and Tidal Energy Conference, 2025)
It has been known that biofouling has notable effects on floating offshore wind turbines (FOWTs) and other marine energy systems which play a critical role in the global development of sustainable energy. For the tropical waters around Taiwan, this is even truer. Its impact on offshore renewable energy systems is manifold, such as drag and weight increase, altered hydrodynamics, corrosion acceleration, and additional maintenance and cleaning costs. In the present study, we focus on its effects on hydrodynamic behavior of a semi-submersible wind turbine system, including mooring systems and cables.The present study utilizes the TaidaFloat platform, a semi-submersible floating platform with a tri-column and off-center turbine placement design, developed by National Taiwan University to support a 15 MW wind turbine. The mooring system consists of three mooring lines attached to each of the three columns, following the guidelines provided by the "ABS - Guide for Building and Classing Floating Offshore Wind Turbines." These guidelines are applicable to sites with a water depth of approximately 70 meters and environmental conditions of the Taiwan Strait, where the majority of the mooring lines and cables ar this depth are prone to marine biofouling.The objective of this study is to evaluate the effects of biofouing mass, diameter, and distribution location on the dynamic behavior of mooring lines for floating wind turbines at shallow water sites. The modeling of biofouling is based on various NORSOK standards and local survey data from Taiwan. The study investigates changes in fatigue damage, offset, tension, and natural frequency under various biofouling conditions.The analysis considers two types of mooring configurations, three sea states, and four biofouling conditions, using OrcaWave and OrcaFlex for simulations. Under the extreme sea conditions, the maximum yaw may increase or decrease by 5%, while the maximum tension in the mooring lines may also vary to some extent. Interestingly, regardless of changes in maximum displacement and tension, fatigue damage consistently increases, with a potential maximum increase of up to 15%. In addition, we also compare results due to typical biofouling in European seas and Taiwan waters.